Terapia de fala com uso de ultrassonografia em casos de anteriorização de fricativas - Rosado, Isadora Mayer (2019)
Objective: To verify the effects of speech therapy using ultrasound biofeedback (US) in a proposal for the intervention of children with speech sound disorders (SSD) that perform the fricatives anteriorization repair strategy. Methodology: The sample was consisted of four children with SSD whom performed this repair strategy and were aged between seven years and nine years and six months old, this age at the beginning of the therapeutic process. All of them underwent general and ultrasonographic speech evaluations, the last one (ultrasonographic) being performed also at different moments of the therapy, as well as the evaluation of the phonology system. The study was proposed by a model formed in periods. Each period contained five sessions, four of which were for therapy with US biofeedback and one for revaluation. Thus, the child performed an initial pre-therapy evaluation, and an evaluation at each end of period. Also, an evaluation was performed 45 days after the end of treatment, in order to verify the occurrence of acquisition, generalization and retention. The first period was devoted to the treatment of sound // in Medial Onset (OM), and the second period for the treatment of // also in OM. From the soundings at the end of the periods 1 (FP1) and 2 (FP2) it was observed whether there had been acquisition or generalization of the sounds worked for the initial onset position (OI) and untrained words in session. If this had not occurred, a period should be performed to stimulate the target sound in the position in which had difficulty to generalize. Results: Only two treatment periods were performed, and all participants performed the acquired sounds, // and // in OM, with generalization for untrained words, and also the acquisition of these sounds in the position of OI. In the retention evaluation, it was verified that the treatment presented satisfactory results for the majority of the participants, being observed that three of the four participants were able to learn the language gestures that were taught to them. Conclusion: The proposed therapy model with ultrasound biofeedback was beneficial for most children, favoring the acquisition, generalization and retention of the treated sounds.